A escola como espaço de reflexão sobre o turismo de base comunitária, através da metodologia da problematização, em Ponte de Itabatinga, Jandaíra, Bahia - Silva, Alda Cristina Menezes da (2022)
Community-based Tourism (TBC) is a way of doing tourism that prioritizes the needs of the place, people, culture and the environment. This dissertation arose from two concerns: the first referred to the role of the school as a space for discussion and reflection on the TBC; and the second corresponded to the establishment of methodological paths to discuss the implementation, organization and strengthening of the TBC with the school and the community. In this sense, the general objective of this research was to analyze the use of the Active Methodology of Problematization, together with the students of the Joana Almeida Pinto Municipal School and people from the surrounding community, in the process of reflection to implement Community-based Tourism, in the community of Ponte de Itabatinga, Jandaíra Municipality, Bahia. Based on this understanding, the specific objectives that led to the dissertation are constituted: to characterize the community of Ponte de Itabatinga in its relations with tourist activity; evaluate the use of the Problematization Methodology in the reflections on the implementation, organization and strengthening of Community-based Tourism, together with the students of the researched school and the community of Ponte de Itabatinga; and produce a primer education for the dissemination of knowledge about Community-based Tourism, through the Problematization Methodology, with the school and the community. The research method was centered on phenomenology, using the qualitative approach. For this, the techniques of data collection were used: bibliographic, documentary, field and "action research". After authorization of the research by the Ethics and Research Committee of the Federal University of Sergipe, the project was presented to school management, students and the community. Then, the activities defined for each stage of the Problematization Methodology were initiated, together with the 12 students of the Joana Almeida Pinto Municipal School and five people from the community. The steps of the methodology followed the order defined by the Arco de Maguerez: in the observation of reality, the participants of the research chose three observation points P1, P2 and P3. The identification of key points was performed in groups in the observation stage. In the theorization, the themes were organized technically and theoretically for the study and investigation of the theme worked. In the chances of a solution, they idealized and executed the drafting of an open letter to the Municipal Environment Secretariat of Jandaíra, Bahia, and the definition of a sustainable route. And in the application to reality they designed the Green Line Route, based on the analysis swot, and proposed the feasibility of delivering the open letter to the Municipal Environment Department of Jandaíra, Bahia. The analysis of qualitative data was guided by the Discourse Analysis method, through which the units of meaning were defined: "Environment, region and meanings"; "Social inclusion"; and "Community-based Tourism". The units of meaning revealed questions and suggestions on the part of the research participants, highlight environmental problems and reflected the "lack of opportunities" which, in turn, excludes several people in a social, economic and political way. Thus, elements were found throughout the stages of the research that can be used as subsidies for the reflection of a future CbT project in the researched community, through a work articulated with the School. The projects include communities in a sustainable way, leading them to have control over the exploitation of natural resources, providing organization, strengthening and leading social actors to be protagonists of their own history.